2014
DOI: 10.1371/journal.pone.0090906
|View full text |Cite
|
Sign up to set email alerts
|

Trail Communication Regulated by Two Trail Pheromone Components in the Fungus-Growing Termite Odontotermes formosanus (Shiraki)

Abstract: The eusocial termites are well accomplished in chemical communication, but how they achieve the communication using trace amount of no more than two pheromone components is mostly unknown. In this study, the foraging process and trail pheromones of the fungus-growing termite Odontotermes formosanus (Shiraki) were systematically studied and monitored in real-time using a combination of techniques, including video analysis, solid-phase microextraction, gas chromatography coupled with either mass spectrometry or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…The complexity of the pheromonal use in termites is evidenced by the change in signal interpretation with changing DDE and DOE ratios. Beyond the data that we provide in this study, the complexity of termite trail pheromones is supported by Wen et al [29], which showed similar patterns for O. formosanus (Macrotermitinae).…”
Section: Discussion (A) Evolution Of Termite Trail-following Behavioursupporting
confidence: 84%
See 2 more Smart Citations
“…The complexity of the pheromonal use in termites is evidenced by the change in signal interpretation with changing DDE and DOE ratios. Beyond the data that we provide in this study, the complexity of termite trail pheromones is supported by Wen et al [29], which showed similar patterns for O. formosanus (Macrotermitinae).…”
Section: Discussion (A) Evolution Of Termite Trail-following Behavioursupporting
confidence: 84%
“…Foraging in termites, and in most ants, is a collective task during which the risk of predation is high. Communication strategies may therefore be used to ensure the efficient gathering of food, such as foraging communication, including the secretion of a trail-following pheromone [27][28][29][30], alarm communication with vibrations or alarm pheromones [31], and nest-mate recognition to avoid mistakes in defensive behaviour [32,33]. To be successful, foraging communication should transmit all the basic information related to the food source, such as quantity, quality, direction and location.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pheromones are important information agents and help to regulate colony behaviour in social insects, such as honey bees (Slessor et al, 2005), ants (Hölldobler, 1995), termites (Wen et al, 2014) and wasps Turillazzi and Bruschini, 2010). Alarm pheromones can play dual roles, by activating nest defence and serving as a warning that allows foragers to avoid dangerous sites.…”
Section: Introductionmentioning
confidence: 99%
“…In most social insects studied to date, alarm pheromones consist of multi-component blends Turillazzi and Bruschini, 2010;Hölldobler, 1995;Slessor et al, 2005;Wen et al, 2014). Hornet alarm pheromones also contain multiple components, some of which are known to elicit alarm behaviour.…”
Section: Introductionmentioning
confidence: 99%